2020
DOI: 10.2166/ws.2020.106
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary nitrogen fractions and source assignment from different inflows to a receiving lake

Abstract: The spatial distribution of the sediment nitrogen in ten typical estuaries of Lake Taihu was determined. A simple quantitative estimation model and principal component analysis (PCA) method were applied to find the source and major factors of estuarine sediment nitrogen loading. The average concentrations of total nitrogen (TN), organic nitrogen (Org-N), ammonium nitrogen and nitrate-nitrogen in the sediments of the ten estuaries were 1315.5, 1220.1, 82.53 and 6.45 mg/kg, with the organic fraction dominating. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The re-distribution of nutrients in lake ecosystems is largely determined by the re-suspension process. Higher water content represents a strong possibility of nutrient releasing to the overlying water (Li et al 2020). The WC ranged from 30.40 to 58.64% in the two areas, and the average WC value in East Lake Taihu was larger than Zhushan Bay (Table 1).…”
Section: Physiochemical Characteristics Of Algae-and Hydrophyte-dominated Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The re-distribution of nutrients in lake ecosystems is largely determined by the re-suspension process. Higher water content represents a strong possibility of nutrient releasing to the overlying water (Li et al 2020). The WC ranged from 30.40 to 58.64% in the two areas, and the average WC value in East Lake Taihu was larger than Zhushan Bay (Table 1).…”
Section: Physiochemical Characteristics Of Algae-and Hydrophyte-dominated Areasmentioning
confidence: 99%
“…The sediment water content (WC) is the indication of sediment compaction conditions, which determines the re-suspension of sediment nutrients (Li et al 2020). The re-distribution of nutrients in lake ecosystems is largely determined by the re-suspension process.…”
Section: Physiochemical Characteristics Of Algae-and Hydrophyte-dominated Areasmentioning
confidence: 99%
“…Although some studies have reported on speciation and distribution of the nutrients (N and P) in river/lake sediment (Li et al, 2012;Shen et al, 2021), the effect of agricultural J o u r n a l P r e -p r o o f intensification on historical nutrient dynamics and source in the sediments (Ni et al, 2015), estimating the flux loads and sources of total N (TN) and total P (TP) by hydrologic surveys and an experimental simulation of suspended sediment (Wang et al, 2017), finding the source and major factors of estuarine sediment N loading by model (Li et al, 2020a), identifying recent sources and fate of sedimentary N in the Baltic Sea based on organic matter elemental composition and N and carbon (C) stable isotopes ratios (Winogradow &Pempkowiak, 2020), and identifying sources and cycling of P in the sediment of inflow rivers (Wang et al, 2021), no information is available about quantitively identifying N and P pollutants-based sediment sources under different land management.…”
Section: Introductionmentioning
confidence: 99%